Applicazioni Copernicus a scala locale per il monitoraggio delle acque di balneazione - Giacomo Martirano (mediaGEO soc. coop., 2019)
TEMAR is a collaborative research project, aimed at the research, development and testing of an innovative service for monitoring and mitigating the risk of pollution of bathing water, of potential interest for a vast use. It is based on the ability of optical remote sensing satellites to detect biochemical and physical characteristics of bathing waters on large surfaces and to validate them by in-situ measurements performed with aquatic drones. The project is co-funded by the Structural Funds of the European Commission, by means of the POR (Operative Regional Programme) Calabria 2014-2020.